2008
DOI: 10.1021/ma7022205
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic Poly(ester urethane)s with Novel Soft Segments

Abstract: A new class of thermoplastic poly(ester urethane)s containing novel soft segments are prepared using a one-step synthesis. Amorphous polyester prepolymers (〈M n 〉 ) 1.5 × 10 3 -3.4 × 10 3 g/mol) were incorporated as soft segments in poly(ester urethane)s using an aromatic diisocyanate, 4,4′-methylenebis(phenylisocyanate), but with no chain extension. These completely amorphous materials had a wide range of mechanical properties (E ) 0.86-29.3 MPa; γ max ) 2106%), and they possessed linear degradation profiles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…7 In solution, the low surface energy soft segments are oriented at the surface while the hydrophobic hard segments remain in the bulk material to minimize the overall surface free energy at the interface. 8 As shown in Figure 1, PPU1 – PPU4 exhibited a surface restructuring phenomena as evidenced by steadily decreasing water contact angles upon exposure to water droplets. After 20 min in water, all contact angles measured decreased from ~80° (t = 0) by approximately 1° min −1 .…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…7 In solution, the low surface energy soft segments are oriented at the surface while the hydrophobic hard segments remain in the bulk material to minimize the overall surface free energy at the interface. 8 As shown in Figure 1, PPU1 – PPU4 exhibited a surface restructuring phenomena as evidenced by steadily decreasing water contact angles upon exposure to water droplets. After 20 min in water, all contact angles measured decreased from ~80° (t = 0) by approximately 1° min −1 .…”
Section: Resultsmentioning
confidence: 89%
“…8 Additionally, the absence of polar thiol functionalities in the hard segments should prevent mixing of hard and soft segments resulting in elastic materials with a high degree of optical clarity. 9 Static water contact angle measurements indicated that thiolation of the polyurethane affected neither the instantaneous surface energy nor the surface reorientation exhibited by most polyurethanes.…”
Section: Resultsmentioning
confidence: 99%
“…Although many SMPUs offer biocompatibility, many groups are attempting to develop new SM materials that offer a combination of the following characteristics: biocompatibility, bioresorbability, biodegradability, and low cytotoxicity, among others. In one study, Pierce and coworkers (15) reported on a thermoplastic poly(ester urethane) that incorporated novel, in-house-synthesized, amorphous oligomeric diols based on aliphatic diols and aliphatic diacids or substituted anhydride as soft segments. In addition to exhibiting low cytotoxicity, their new poly(ester urethane)s showed an extraordinary high elongation at break of 2106%.…”
Section: New Materials and Shape Memory Behaviormentioning
confidence: 99%
“…27 The material properties (physical and chemical) can be tailored by optimizing their HS and SS composition as well as their functionalities. Due to its nontoxic nature, its wide range of mechanical properties (good flexibility, high modulus, toughness) and its excellent biocompatibility, TPU has been used in various medical devices, such as catheters, heart valves, bladders, tubing, blood filters, implants and wound dressings; 28 the first successful polyurethane-based biomedical device was commercialized in 1970. 29 However, it has been observed that for long-term and dynamic applications, especially in cardiovascular systems, virgin TPU has a limited usage due to its poor mechanical properties.…”
Section: Introductionmentioning
confidence: 99%